Marginal employment' and the demand for heterogenous labour: Empirical evidence from a multi-factor labour demand model for Germany - Ronny Freier; Viktor Steiner (Institute for the Study of Labor (IZA), 2007)
We develop a structural multi-factor labour demand model which distinguishes between eight labour categories including non-standard types of employment such as marginal employment. The model is estimated for both the number of workers and total working hours using a new panel data set. For unskilled and skilled workers in full-time employment, we find labour demand elasticities similar to previous estimates for the west German economy. Our new estimates of own-wage elasticities for marginal employment range between -.4 (number of male workers in west Germany) to -1 (working hours for women). We illustrate the implications of these estimates by simulating the likely labour demand effects of the recent increase of employers' social security contributions (SSC) on marginal employment in Germany.
urn:nbn:de:101:1-20080425170
Keywords: 330; Arbeitsnachfrage; Ungeschützte Beschäftigung; Sozialversicherungsbeitrag; Beschäftigungseffekt; Schätzung; Deutschland